2009
DOI: 10.1016/j.sdentj.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cariostatic effects of various iron supplements on the initiation of dental caries

Abstract: It was concluded that iron may have cariostatic effect on the in vitro development of dental caries in human teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In the present study, the iron concentration representing the entire iron element in saliva was detected, including iron(II) and iron(III). Iron(III) complex addition has been reported to have no cariostatic effect ( 43 ). Therefore, different valences of iron should be considered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the iron concentration representing the entire iron element in saliva was detected, including iron(II) and iron(III). Iron(III) complex addition has been reported to have no cariostatic effect ( 43 ). Therefore, different valences of iron should be considered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the benefits of FS on tooth enamel 5,6,9 . A previous work subjected bovine enamel blocks to cariogenic challenges and to FS (15 mmol/L -1 ) and they reported a significant reduction in mineral loss of enamel and a change in phosphate concentration at the biofilm 9 , whereas another work evaluated the cariostatic effect of iron supplements at different concentrations (100% and 50%) on extracted human permanent teeth and observed a reduction in enamel demineralization after their use 6 . Moreover, other authors suggest that FS at 18 µg/mL compared with different concentrations (0.33, 0.840, and 70.0 µg Fe/mL) had better results in reducing enamel demineralization in bovine enamel 5 .…”
Section: Authors Contributionmentioning
confidence: 99%
“…FS has been analyzed in several studies in dentistry [5][6][7][8][9][10][11][12][13] using artificial dental models (mainly bovine teeth and human permanent teeth). The most frequently reported properties include reduction in the degree of enamel dissolution 5,8,13 , reduction of dental erosion 7,12 , alterations in biofilm composition (in situ) 9,10,14 , and oxidative modifications in glucosyltransferase promotion 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations